Cognitive status and quality of life of post-stroke patients: evidence from Serbia - Biševac, Emir; Safiye, Teodora; Mahmutović, Elvis (Vojnosanitetski pregled, 2025)
Background/Aim. Stroke is a major global health problem, and more than half of stroke patients suffer from cognitive impairments. The aim of this study was to assess the impact of secondary rehabilitation on cognitive status and to examine its correlation with quality of life in post-stroke patients. Methods. A total of 100 patients (average age 66.5 ± 7.3 years) participated in the study, of whom 50 were diagnosed with ischemic stroke (IS) and 50 with intracerebral hemorrhagic stroke (ICH). The Mini-Mental State Examination (MMSE) was utilized to assess cognitive status, while the European Quality of Life (EuroQol) 5-dimensional 3-level (EQ-5D-3L) questionnaire was employed to evaluate quality of life. Results. The MMSE test results showed significant differences at three months (p = 0.037) and six months (p = 0.009) of secondary rehabilitation compared to admission. For the EQ-5D-3L, significant differences were observed at the time of admission (p < 0.001), one month (p = 0.001), and six months (p = 0.007). In addition, the Wilcoxon signed-rank test showed a statistically significant improvement in both MMSE and EQ-5D-3L scores when comparing results from admission to those taken one month (p < 0.001), three months (p < 0.001), and six months (p < 0.001) after secondary rehabilitation for both IS and ICH. Conclusion. The results indicate a significant correlation between cognitive status and quality of life, measured at all four time points. Additionally, it was found that a longer duration of secondary rehabilitation leads to improved cognitive status and a higher quality of life for post-stroke patients.
Keywords: cognition disorders; hemorrhagic stroke; ischemic stroke; rehabilitation; quality of life.